Phosphorylation sites at the C-terminus of the platelet-derived growth factor receptor bind phospholipase C gamma 1. - Kashishian, A (1993)
We have identified two tyrosine phosphorylation sites, Tyr 1009 and Tyr 1021, in the C-terminal noncatalytic region of the human platelet-derived growth factor (PDGF) receptor beta subunit. Mutant receptors with phenylalanine substitutions at either or both of these tyrosines were expressed in dog epithelial cells. Mutation of Tyr 1021 markedly reduced the PDGF-stimulated binding of phospholipase C (PLC) gamma 1 but had no effect on binding of the GTPase activator protein of Ras or of phosphatidylinositol 3 kinase. Mutation of Tyr 1009 reduced binding of PLC gamma 1 less severely. Mutation of Tyr 1021, or both Tyr 1009 and Tyr 1021, also reduced the PDGF-dependent binding of a transiently expressed fusion protein containing the two Src-homology 2 domains from PLC gamma 1. Mutation of Tyr 1021, or both Tyr 1009 and Tyr 1021, greatly reduced PDGF-stimulated tyrosine phosphorylation of PLC gamma 1 but did not prevent the tyrosine phosphorylation of other cell proteins, including mitogen-activated protein kinase. We conclude that Tyr 1021, and possibly Tyr 1009, is a binding site for PLC gamma 1.